High rate Li-ion storage properties of MOF-carbonized derivatives coated on MnO nanowires. (14th June 2017) - Huang, Zhen-Dong; Gong, Zhen; Kang, Qi; Fang, Yanwu; Yang, Xu-Sheng; Liu, Ruiqing; Lin, Xiujing; Feng, Xiaomiao; Ma, Yanwen; Wang, Dan
Abstract : Carbonized derivatives of ZIF-67 MOFs on MnO2 NWs are fabricated as high rate Li-ion storage anode materials. Abstract : Recently, metal–organic framework (MOF) derived porous carbon-based composites have become one of the most advanced electrode materials for high performance energy storage systems. In this work, zeolitic imidazolate framework (ZIF) types of MOF strung by MnO2 NWs, forming an interesting structure like Chinese candied hawthorn fruit on a stick, are used as precursors to prepare C/Co-coated MnO nanowires (C/Co-MnO NWs). It is interesting and exciting to observe that the simultaneously formed carbon coating derived from the ZIFs significantly promotes the cyclic and rate performances of manganese oxide because of the synergistic effect of the highly conductive uniform carbon coating and the high capacity contribution from the MnO NWs. The obtained C/Co-MnO NWs could deliver 848.4 and 718 mA h g −1 at 500 and 5000 mA g −1 after 40 charge/discharge cycles, respectively, which is superior to other reported MOF-derived nanostructured materials, and makes it a very promising candidate anode material for future high-power lithium ion batteries.